Transition-metal-catalyzed additions of C-H bonds to C-X (X = N, O) multiple bonds via C-H bond activation - Yan, Guobing; Wu, Xiangmei; Yang, Minghua (Organic & biomolecular chemistry, 2013)
Chemical transformations via catalytic C-H bond activation have been established as one of the most powerful tools in organic synthetic chemistry. Transition-metal-catalyzed addition reactions of C-H bonds to polar C-X (X = N, O) multiple bonds, such as aldehydes, ketones, imines, isocyanates, nitriles, isocyanides, carbon monoxide and carbon dioxide, have undergone a rapid development in recent years. In this review, recent advances in this active area have been highlighted and their mechanisms have been discussed. A review highlighting recent advances and mechanisms of transition-metal-catalyzed addition reactions of C-H bonds to polar C-X (X = N, O) multiple bonds, such as aldehydes, ketones, imines, isocyanates, nitriles, isocyanides, carbon monoxide and carbon dioxide.